Developing scale on factors affecting innovation service culture in hospitality industry - A. Rahim, Marina; Kunasekaran, Puvaneswaran; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Social Transformation Research Platform, Universiti Sains Malaysia, 2012)
This paper aimed at finding the factors influencing innovative service culture and personality, a case study of a famous hotel in Kuala Lumpur. In order to achieve the aim, the objectives were laid out firstly identify the factors influencing the innovative service culture at and secondly to develop a measurement scale on the factors influencing innovation. Past studies on innovation, innovative culture and innovative service were reviewed. A sample size of 143 respondents was interviewed to. Factor analysis was employed to develop a scale on the factors influencing innovative service culture. The aim of the results was to reduce the number of variables, to the important variable only. From 72 variables, only 49 were selected in the factor analysis through a rotated component matrix. Later, they were regrouped into 9 factors, according to their similarity of characteristics and justifications (service culture, proactive personality, group dynamics, and sense of belongings, corporate communications, and involvement and exceeding expectations). Though the objectives of this research were met, further research has to be carried out to determine significant demographic factors and to observe the relationships to the various factors that the researcher has developed.